2019
DOI: 10.1039/c9gc03045j
|View full text |Cite
|
Sign up to set email alerts
|

Direct C–H sulfenylation of quinoxalinones with thiols under visible-light-induced photocatalyst-free conditions

Abstract: We have developed a metal-free and catalyst-free visible-light-promoted direct C–H sulfenylation of quinoxalin-2(1H)-ones with thiols for the synthesis of diverse 3-sulfenylquinoxalin-2(1H)-ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(37 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…Regarding the direct formation of C-S bonds, in late 2019, Pan and collaborators reported a visible-light-enabled photocatalyst-free protocol for the sulfenylation of quinoxalin-2-ones with thiols. [71] After screening some photocatalysts, they realized that the reaction could proceed without photocatalyst. Therefore, the researchers optimized the reaction conditions between quinoxalin-2-one and p-mercaptoanisole under catalyst-free conditions, and they found out that conducting the transformation in NMP at 50°C under the irradiation of Blue LEDs allows them to obtain the desired product in 76 % yield while diminishing the amount of p-mercaptoanisole dimer formation.…”
Section: Eurjocmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the direct formation of C-S bonds, in late 2019, Pan and collaborators reported a visible-light-enabled photocatalyst-free protocol for the sulfenylation of quinoxalin-2-ones with thiols. [71] After screening some photocatalysts, they realized that the reaction could proceed without photocatalyst. Therefore, the researchers optimized the reaction conditions between quinoxalin-2-one and p-mercaptoanisole under catalyst-free conditions, and they found out that conducting the transformation in NMP at 50°C under the irradiation of Blue LEDs allows them to obtain the desired product in 76 % yield while diminishing the amount of p-mercaptoanisole dimer formation.…”
Section: Eurjocmentioning
confidence: 99%
“…Surprisingly, they reported that this transformation does not proceed without photocatalyst, as opposed to the Pan work. [71] The researchers applied the optimized reaction conditions to other differently substituted quinoxalin-2-ones and distinct thiols, with forty examples including a variety of aliphatic thiols and quinoxalinones bearing electron-donating (Me) and electron-withdrawing groups (F, Cl, CO 2 Me, CF 3 , NO 2 ) (Scheme 52). The applicability of the thioetherification protocol was confirmed on a gram scale under…”
Section: Eurjocmentioning
confidence: 99%
See 2 more Smart Citations
“…Some bioactive molecules containing quinoxalin-2(1 H )-one skeleton, such as Compounds 1 - 3 , also show potential applications in medicinal chemistry fields (Meyer et al, 2006 ; Khattab et al, 2015 ; Qin et al, 2015 ) ( Figure 1A ). Because of their synthetic usefulness and potential biological importance, the introduction of functional groups into the C3-position of the quinoxalin-2(1 H )-ones has already become a research hotspot, and various protocols for the direct C3-H functionalization of quinoxalin-2(1 H )-ones have been reported (Ebersol et al, 2019 ; Gu et al, 2019 ; Hong et al, 2019 ; Li et al, 2019 ; Peng et al, 2019 ; Rostoll-Berenguer et al, 2019 ; Teng et al, 2019 ; Wang et al, 2019a , 2020 ; Xie et al, 2019b ; Zhao et al, 2019 ; Zheng and Studer, 2019 ; Tian et al, 2020 ; Yuan et al, 2020 ). In particular, the C3-H functionalization of quinoxalin-2(1 H )-ones involving hypervalent iodine reagents has drawn wide attention for the aforementioned advantages of hypervalent iodine reagents, mainly including arylation (Paul et al, 2017 ; Yin and Zhang, 2017 ), trifluoromethylation (Wang et al, 2018 ; Xue et al, 2019a ), alkylation (Wang et al, 2019b ; Xie et al, 2019a ; Xue et al, 2019b ; Shen et al, 2020 ), and alkoxylation (Xu et al, 2019 ; Yang et al, 2019 ) of quinoxalin-2(1 H )-ones, which provide convenient and environmentally friendly means for the synthesis of 3-substituted quinoxalinone derivatives.…”
Section: Introductionmentioning
confidence: 99%